2017
DOI: 10.1093/mnras/stx2525
|View full text |Cite
|
Sign up to set email alerts
|

The SDSS-DR12 large-scale cross-correlation of damped Lyman alpha systems with the Lyman alpha forest

Abstract: We present a measurement of the DLA mean bias from the cross-correlation of DLA and the Lyα forest, updating earlier results of Font-Ribera et al. (2012) with the final BOSS Data Release and an improved method to address continuum fitting corrections. Our cross-correlation is well fitted by linear theory with the standard ΛCDM model, with a DLA bias of b DLA = 1.99 ± 0.11; a more conservative analysis, which removes DLA in the Lyβ forest and uses only the cross-correlation at r > 10 h −1 Mpc, yields b DLA = 2.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 74 publications
15
82
0
Order By: Relevance
“…The horizontal grey band is the redshift-average value from ref. [19]. The inset shows the same bias prediction from our models up to z = 6.…”
Section: Model Asupporting
confidence: 59%
See 1 more Smart Citation
“…The horizontal grey band is the redshift-average value from ref. [19]. The inset shows the same bias prediction from our models up to z = 6.…”
Section: Model Asupporting
confidence: 59%
“…Squares with error bars are the measurements from ref. [19] while the circles and line show the predictions from our models. The horizontal grey band is the redshift-average value from ref.…”
Section: Model Amentioning
confidence: 90%
“…Furthermore, Font-Ribera et al (2012), using the SDSS-III Baryon Oscillation Spectroscopic Survey (BOSS), found an unexpected large linear bias of DLAs (b DL A = 2.17 ± 0.20, with an assumption on the bias of the Lyα forest) by cross-correlating these absorbers with the Lyα forest. This measurement was more recently updated by Pérez-Ràfols et al (2018b), who found a linear bias of b DL A = 2.00 ± 0.19, which is only slightly lower than the clustering amplitude of Lyman Break Galaxies (LBGs; see also Cooke et al 2006). This value of the bias, which implies masses of 10 11 M , appears uncomfortably high for some galaxy formation simulations and models (see e.g Pontzen et al 2008; Barnes & Haehnelt 2014;Padmanabhan et al 2017) if DLAs sample a very wide range in galaxy sizes (e.g.…”
mentioning
confidence: 99%
“…We first determine potential HCD locations by computing a threshold value of the Gaussian field, set by an input bias b HCD (z). In our realisations, we choose b HCD (z) = 2.0 to be constant with redshift, and in line with [62]. This picks out peaks in the field that are sufficiently dense to host an HCD.…”
Section: Adding Hcdsmentioning
confidence: 99%
“…Making such an extreme cut in rest-frame wavelength greatly reduces the number of HCDs in our catalogue. In this work we use approximately 30 times the number of skewers 10 It should be noted that [62] includes only HCDs at least 5000 km/s away from their host quasar, equivalent to a rest-frame wavelength cut of approximately 1195Å. We choose to use λr,HCD < λLyα in the right panel of Figure 6 in order to explain the relationship between the geometry of the problem and the observed effect more clearly.…”
Section: The Lyα-hcd Cross-correlationmentioning
confidence: 99%